SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS PENDEKATAN METAKOGNITIF TERHADAP PENINGKATAN KEMAMPUAN PENALARAN MATEMATIK SISWA - Adelia, Dita; Nindiasari, Hepsi; Yuhana, Yuyu (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Mathematical reasoning ability is an important ability that students must master, but this ability is still relatively low. The aim of this research is to determine the effectiveness of the metacognitive approach on students' mathematical reasoning abilities. The method used in this research is Systematic Literature Review (SLR). This research used 19 articles from 2018 to 2023 sourced from national and international journals, namely 16 articles with a Sinta index, 2 articles from Google Scholar, and 1 international proceedings journal. The results of the SLR research show that the implementation of the metacognitive approach has an effective impact on students' mathematical reasoning abilities. The metacognitive approach can train students to develop mathematical reasoning abilities